PENAFSIRAN AL-QUR’AN TENTANG RESILIENSI SPIRITUAL GENERASI Z DALAM KRISIS IDENTITAS KEAGAMAAN DIGITAL - Muhammad Zaki Hidayat; Bashori (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2025)
The rapid development of digital technology has significantly influenced the religious orientation of Generation Z, including the emergence of a crisis in religious identity. Living amid open and fast-paced information flows, Generation Z is increasingly exposed to narratives that are not always aligned with traditional Islamic values, resulting in spiritual disorientation and unstable religious identity. This study aims to examine how the interpretation of the Qur'an, particularly through a thematic (mawḍū‘ī) approach, by identifying Qur’anic verses related to spiritual resilience, classifying them into subthemes (patience, trust, consistency), and anlyzing their relevance to Generation Z identify in digital era. This research adopts a qualitative method based on library research, employing thematic interpretation of selected Qur'anic verses related to psychological and spiritual endurance. Thus, the Qur'an serves not only as a normative text, but also as a source of spiritual strength that offers solutions to the crisis of religious identity among Generation Z. This study contributes theoretically to the development of a contextual thematic exegesis approach, and practically to the reinforcement of Qur’an based religious education in the digital era.